Gender bias on the effects of instruction on kinematic and kinetic jump parameters of high-level athletes - Walsh, M. S.; Waters, J.; Kersting, U. G. (Research in Sports Medicine, 2007)
The purposes of this study were to examine gender differences during drop jumps, to evaluate the effect of a set of simple instructions on kinematic and kinetic parameters during a drop jump, and to determine if there are gender differences in the effects of instruction on those parameters. Twenty-five basketball players, 13 men and 12 women, performed drop jumps from a box (height 30.5 cm) after being asked to perform a land and jump movement as they normally would do when aiming at maximum jump height. The experimental group received a set of instructions designed to make them land softer. The measured parameters were impact force at landing, ground contact time, flight time, frontal plane knee angle, sagittal plane knee angle, and distance between the knees. When the groups were examined by gender, no differences in the parameters were seen in men after instruction, but in women the following significant differences were detected: an increase in contact time, a decrease in landing force, and a decrease in inward movement of the knees after landing. These data indicate that females respond differently to jumping/landing instructions.